Key environmental features of pharmaceuticals and their metabolites - Боксал, А.; Аубакирова, Б.Н.; Бейсенова, Р.Р.; Хантурин, М.Р. (Fundamental and Experimental Biology, 2015)
The present article describes main characteristics of pharmaceuticals and their metabolites. The author considered the results of existing research and defined the adverse effects of pharmaceuticals to living organisms. It was founded out that drugs can deteriorate some functions of living organisms. It can be concluded that it is important to conduct a study on toxicity of pharmaceuticals and their metabolites to living organisms.